Desenvolvimento de um Recurso Rducacional Digital (RED) de Língua portuguesa fundamentado na base nacional comum Curricular - Hitzschky, Rayssa Araújo (2019)
The BNCC (short for Common Curricular National Base in Portuguese) has triggered the need for new organizational demands for the development of Digital Educational Resources (DER), in order to fulfill the learning objectives listed in this document. In this context, the pedagogical nature of the process becomes even more relevant; however, often the focus of DER development and the studies on the area are restricted to implementation-focused discussions while neglecting key pedagogical points. Thus, this work intends to ease the understanding of the pedagogical aspects involved in the development process of DER based on the BNCC for the teaching of the Portuguese Language. The specific objectives of this work are: a) to investigate the inception of the pedagogical aspects in each one of the stages of the process, b) to investigate the pedagogical strategies adopted during the development of DER, and finally c) analyze the challenges faced by the pedagogical team throughout development. The theoretical framework has been based on studies on the development of DER, which have focused on the pedagogical perspective, as well as on discussions on BNCC for the Portuguese Language related to digital technologies. The research, of the case study type, used the qualitative approach with an interpretative focus. Data collection instruments included participant observation, field diaries, document analysis, and semi-structured focal interview. The results have been broken down according to categories that have emerged during data analysis. The first category, Theoretical alignment, comprises the pedagogical aspects of the structuring of the DER based on fundamentals of a theoretical aspect. The next category, Pedagogical intentionality, involved the choices related to resource planning that had either educational purposes or motivations. The last category, Technical-pedagogical consistency, showed the relationship established between the beginning of the development of DER and its guide and its definitive versions, based on the pedagogical refinement of the final product. The results evidenced a concatenation of pedagogical aspects that marked the necessary paths for the accomplishment of the main purpose of the resource. Moreover, the correlation between the previous studies, the inception of activities, the visual elements and the final revision is what made such observation possible.